Conservative management of the post-traumatic stiff elbow: a physiotherapist's perspective. Issue 2 (April 2016) - Jones, Val
Elbow stiffness is a common consequence following trauma with the management of this condition posing a challenge to therapists and surgeons alike. This paper discusses the role of conservative treatment, such as exercise and splinting, in the prevention and management of the stiff elbow, along with a review of available evidence, to justify their usage.